2004
DOI: 10.1007/s00395-004-0505-4
|View full text |Cite
|
Sign up to set email alerts
|

Trimetazidine protects isolated rat hearts against ischemia?reperfusion injury in an experimental timing ? dependent manner

Abstract: The present study investigated the tolerance of the isolated rat heart to ischemia-reperfusion after administration of trimetazidine (TMZ) at different experimental phases, as well as the possible involvement of p38 MAPK and JNKs in this response. Isolated rat hearts were perfused in Langendorff mode. Untreated hearts after stabilization (S) were subjected to 20 min of zero-flow global ischemia (I) and 45 min of reperfusion (R), (NORM), n = 9. TMZ (10(-5) M) was administered (in the perfusate): a) only at S ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…The result of the present study indicated that TMZ, TMZ-NH, or TMZ-⌽NH treatments did not show significant differences in the activation of p38 MAPK and ERK1/2 during ischemia and I/R. In support of this observation is a recent study by Pantos et al (2005), showing that the cardioprotective effect of TMZ is not mediated through p38 MAPK and c-Jun NH 2 -terminal kinase signaling cascades. Although the findings of the present study revealed that TMZ-NH or TMZ-⌽NH did not affect ERK1/2 and p38 MAPK pathways significantly, the ERK1/2 or p38 MAPK pathway in the protective action of TMZ-NH or TMZ-⌽NH is not ruled out.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The result of the present study indicated that TMZ, TMZ-NH, or TMZ-⌽NH treatments did not show significant differences in the activation of p38 MAPK and ERK1/2 during ischemia and I/R. In support of this observation is a recent study by Pantos et al (2005), showing that the cardioprotective effect of TMZ is not mediated through p38 MAPK and c-Jun NH 2 -terminal kinase signaling cascades. Although the findings of the present study revealed that TMZ-NH or TMZ-⌽NH did not affect ERK1/2 and p38 MAPK pathways significantly, the ERK1/2 or p38 MAPK pathway in the protective action of TMZ-NH or TMZ-⌽NH is not ruled out.…”
Section: Discussionsupporting
confidence: 83%
“…TMZ decreases oxidative damage to mitochondria and protects hearts from I/R-induced damage to mitochondrial respiration (Guarnieri and Muscari, 1993). TMZ also showed cytoprotective effect in several models of myocardial infarction (Harpery et al, 1989;Pantos et al, 2005). Recently, it has been shown that TMZ protected postischemic hearts by inhibiting the activation of neutrophils (Tritto et al, 2005).…”
mentioning
confidence: 99%
“…At the cellular level, TMZ preserves ATP production, reduces the generation of oxygen free radicals (Maupoil et al, 1990;Gambert et al, 2006;Kutala et al, 2006), and reduces intracellular acidosis and calcium overload (Kantor et al, 2000). TMZ has been shown to protect hearts from ischemia-induced electrical dysfunction leading to ventricular fibrillation (Vaillant et al, 2008), ischemia-reperfusion-induced damage to mitochondrial respiration (Guarnieri and Muscari, 1993), and ischemia-reperfusion injury by decreasing myocardial lactate content early at reperfusion (Pantos et al, 2005). Tritto et al (2005) demonstrated that TMZ attenuated tissue injury in postischemic hearts by inhibiting the activation of neutrophils.…”
Section: Preconditioning Of Mscs With Trimetazidine For Cell Therapy 547mentioning
confidence: 99%
“…It reduces oxidative damage to the mitochondria and protects the heart from I/R-induced damage arising from mitochondrial respiration (Guarnieri and Muscari, 1993). TMZ has also shown cytoprotective efficacy in several models of myocardial infarction (Harpery et al, 1989;Pantos et al, 2005). In addition to its beneficial effects in the treatment of I/R injury, TMZ has been reported to provide modest protection to postischemic hearts by improving left ventricular function in patients with chronic coronary artery disease or ischemic cardiomyopathy and in patients experiencing acute periods of ischemia when undergoing percutaneous transluminal coronary angioplasty (McClellan and Plosker, 1999).…”
mentioning
confidence: 99%